2020
DOI: 10.3390/ma13214872
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Laser Post-Processing for the Surface Functionalization of Additively Manufactured Ti-6Al-4V Parts

Abstract: Laser powder bed fusion (LPBF) is one of the additive manufacturing methods used to build metallic parts. To achieve the design requirements, the LPBF process chain can become long and complex. This work aimed to use different laser techniques as alternatives to traditional post-processes, in order to add value and new perspectives on applications, while also simplifying the process chain. Laser polishing (LP) with a continuous wave laser was used for improving the surface quality of the parts, and an ultrasho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The effects of altering the numbers of laser-scanning passes (5,10,15,20,25 and 30 passes) and pulse energies (0.36, 0.53 and 0.71 mJ) were studied. A plot of crater depth as a function of the number of laser passes for the three different pulse energies is shown in Figure 5, demonstrating an almost linear trend within the parameter space tested.…”
Section: Impact Of Laser Pulse Energy and Amount Of Passesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of altering the numbers of laser-scanning passes (5,10,15,20,25 and 30 passes) and pulse energies (0.36, 0.53 and 0.71 mJ) were studied. A plot of crater depth as a function of the number of laser passes for the three different pulse energies is shown in Figure 5, demonstrating an almost linear trend within the parameter space tested.…”
Section: Impact Of Laser Pulse Energy and Amount Of Passesmentioning
confidence: 99%
“…As a result, many research groups have focused their efforts on laser surface texturing to achieve different functional surfaces. This includes surface modification for aesthetic purposes [6,7], encryption of information [8], facilitating other processes (e.g., laser welding of dissimilar metals [9,10]), altering water-repellent properties [5,11,12], generating anti-icing [13] and anti-bacterial [14] surfaces, and modifying the tribological properties of surfaces, in particular reducing wear [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the two steps resulted in hydrophobic characteristics for the surface. In the work, it has also been demonstrated that the biocompatibility of the parts isn't negatively affected despite the treatments [57].…”
Section: Laser Polishing On Am Metal Alloysmentioning
confidence: 99%
“…However, in case of selective surface texturing or surface modification subtractive methods become more advantageous. Especially the combination of AM and laser ablation provide new opportunities in designing of 3D objects with local functionalities and biocompatibility as required for medical implants [9]. In section "14.4 -Laser Post-Processing of additive manufactured parts" recent progress in this approach will be presented and discussed referring to biomedical surfaces and Ventricular Assist Devices (VAD).…”
Section: -Short Overview Of Am Processes and Respective Applicationsmentioning
confidence: 99%
“…In addition to material development, additive manufacturing offers great design freedom in component design, which can be used, for example, for the development of load-optimized designs based on the bionic principle [5]. To add up to the versatility of additive manufacturing, laser post-processes can be used to modify the resulting surfaces of parts produced with such technology [6][7][8][9]. The different types of laser sources commercially available assure their suitability in a wide range of applications, with continuous wave (cw) lasers being often used for reduction of surface roughness, while pulsed lasers being applied in the modification of surface functionalities and to enhance the geometry accuracy.…”
Section: -Introductionmentioning
confidence: 99%